Recent Advances in Photoacid Catalysis for Organic Synthesis - Saway, Jason; Salem, Zena M.; Badillo, Joseph J. (Synthesis, 2020)
Photoacids are molecules that become more acidic upon the absorption of light. This short review highlights recent advances in the use of photoacids as catalysts for organic synthesis. Photoacid-catalyzed transformations discussed herein include: Protonation, glycosylation, acetalization, and arylation reactions.1 Introduction2 Protonation: Excited-State Proton Transfer (ESPT)3 Glycosylation4 Acetalization5 Friedel–Crafts Arylation6 Additional C–C and C–S Bond-Forming Reactions7 Conclusion
Keywords: photoacid catalysis; photochemistry; light-activation; in situ acid generation; excited-state proton transfer (ESPT) catalysis